G294(P) Health and disease in children of the ' irish traveller' community. (12th March 2018) - O'Reilly, P; Jenkinson, A; Martin, T; Stone, G; Power, B; Murphy, AM
Abstract : Background and aims: Irish Travellers are a Roman Catholic endogamous minority group believed to originate from the 12th century whose ethnicity was finally recognised by the Irish Government in March 2017. Latest estimates put their numbers at 40 129 on the island of Ireland, 15 000 in the United Kingdom, 6000 on Mainland Europe and 7000 in America. Nomadism and family are core features of their identity. Early and arranged marraige, frequent child bearing and consanguinity are cultural norms. Our aim was to collate current data on morbidity and mortality of Traveller children with a view to planning of services and provision of healthcare for this population in our region. Methods: A Literature and database(s) search was conducted and relevant clinicians contacted in an effort to compile data on the complexity and heterogeneity of the moden Irish Traveller Community to inform appropriate action in the area of Traveller Child Health. Results: Almost 50% of the Irish Traveller population are children under 15 years of age. Between 650 and 850 Traveller babies are born on the island of Ireland every year. The infant mortality rate is 3.5 times that of the general population. 10% of Traveller children are dead before their second birthday. Main causes of mortality are accidents, congenital malformations and inherited metabolic disorders. To date 93 different genetic disorders are reported, 82 of which the genetic basis is known. There are 60 founder mutations. The commonest disorders are Galactosemia, Hurler Syndome and I-Cell disease, the carrier frequency for which is 1/11, 1/11 and 1/15 respectively. Our study highlights the huge disease burden imposed on these children by the combination of curcumstances of poverty, increased frequency of genetic disorders in consanguineous communities, peripatetic lifestyle, nomadic mindset, superstition, stigma and distrust and provides useful epidemiological information with particular reference to the healthcare needs of minority groups marginalised in our society.